The Solow residual as a black box : attempts at integrating business cycle and growth theories - Mata, Tiago (2022)
The intersection between growth and business cycle theory remains a controversial subject in economics. The question posed by this article is, What role did Robert Solow’s “Technical Change and the Aggregate Production Function” (1957) play in recent attempts to integrate business cycle and growth theory? We argue that the “Solow residual” was a resource given to multiple uses, at times rhetorical and symbolic, at times instrumental for theory development, at others a social artifact. On the history of models that bring growth and fluctuation into a single frame, we have focused on the uses and meanings of a particularly prominent object: the Solow residual. The significance of Solow’s 1957 work arose from having stabilized a method and result, the residual as reproducible object, a black box. This object was shown to traffic liberally across doctrinal divides in economics. Once on offer, the black box had a life of its own. Its relation to the original context and to the intentions and beliefs of its originator was severed. So while Denison used the residual in ways that were surely faithful to Solow, the new classicals employed it in ways that seemed counter to Solow’s outlook. While the residual had always remained a problematic result in growth accounting, its borrowing by real business cycle theorists sought to establish it as a definitive representation of technology. Furthermore, in these models it was a short-run and stochastic technology, a novel and surprising interpretation